2014
DOI: 10.2355/isijinternational.54.342
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of a Numerical Model for Continuous Casting of Steel: Model Theory, Setup and Comparison to Physical Modelling with Liquid Metal

Abstract: Recent developments of an advanced numerical model for Continuous Casting of steel unveiled at the previous 2010 CSSCR Conference in Sapporo, Japan are presented. These include coupling of the existing multiphase, heat transfer and solidification model to argon injection for tracking bubble trajectories in the SEN, metal bulk and across the slag bed after passing through the metal surface. Hence, description of a method for adding gas injection in combination with a multiphase model for tracking metal/slag int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Significant modeling efforts have been made to resolve the meniscus region by a Volume Of Fluid (VOF) approach. [44][45][46][47] The standing wave has been observed in water models and actual caster. The shape of these wave keeps fluctuating depending upon flow in the mold cavity.…”
Section: Thermal Fluid Flow In the Moldmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant modeling efforts have been made to resolve the meniscus region by a Volume Of Fluid (VOF) approach. [44][45][46][47] The standing wave has been observed in water models and actual caster. The shape of these wave keeps fluctuating depending upon flow in the mold cavity.…”
Section: Thermal Fluid Flow In the Moldmentioning
confidence: 99%
“…Shell thinning effect due to curved nature of mold was quantified in order to prevent a break out situation. Lopez [39][40][41]44,45,93) extended the shell growth modeling in presence of multiphase and included real caster dynamics of slag infiltration with oscillation. The model revealed the initial solidification mechanism and formation of oscillation marks.…”
Section: )mentioning
confidence: 99%
“…The results have shown that coupling the bidirectional interactions was essential to get realistic results, especially in the presence of large gas bubbles. Lopez used the DPM Lagrangian model and VOF multiphase model to predict the multiphase (steel‐slag) flow dynamics coupled with argon injection within the CC mold . It proved that the coupling of the DPM technique to an existing CC model based on the multiphase VOF method is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction between the liquid and powder mold slag layers with the molten steel at the top surface of the mold, and the changing shape of that interface, also requires a multiphase flow analysis. [23][24][25][26][27] Stabilizing this interface to avoid excessive surface velocities, level fluctuations and profile variations is of critical importance to avoiding slag entrainment, achieving uniform slag infiltration, and avoiding surface defects, which are important to obtaining quality in the continuous-cast product. 28,29) The solidified shell is another solid phase to consider in the analysis of mold flow as the shape of the solid shell can affect the flow pattern 30) and the capture of particles such as bubbles.…”
Section: Introductionmentioning
confidence: 99%